(untitled) (Research, Society and Development, 2020)
Antimicrobial resistance and the consequent inefficiency of antibiotics are the main problems faced by medicine. In view of this, numerous researches have been aimed at looking for new agents with antibacterial activity, among them natural products. Thus, this study aims to evaluate the antioxidant activity of aqueous and hydroalcoholic extracts of the leaves and roots of Spondias tuberosa by Thin Layer Chromatography (TLC), as well as to verify the antibacterial action of the extracts alone and in combination with commercial antibiotics to evaluate its potential in action of change of antibiotics. The extracts showed polar and nonpolar phenolic substances with antioxidant action. The Minimum Inhibitory Concentration (MIC) of the hydroalcoholic extracts of the leaves and roots was 1,024 μg/mL compared to the Staphylococcus aureus 25923 strain, whereas with the other strains, the products showed an MIC ≥ 2,048 µg/mL. The effect of combining extracts with amikacin, ampicillin and norfloxacin against the multidrug-resistant bacteria Escherichia coli 06, Staphylococcus aureus 10 and Pseudomonas aeruginosa 24 resulted in synergistic effects with aminoglycoside alone, achieving up to 75 % reduction in the MIC of the antibiotic. In view of the results obtained, it can be concluded that the extracts of S. tuberosa presented polar and nonpolar phenolic substances, in the antibacterial activity it can positively modify the effect of the aminoglycoside antibiotic against multi-resistant bacteria, but future studies are necessary to discover the mechanism of action of such an effect.